Smart Nutrition for Futsal: Pengaruh Edukasi Digital terhadap Perubahan Perilaku Pola Makan dan Hidrasi Atlet Futsal Usia Dini - Putri Amilasari; Oftafiana Elsa; Uyun Aminatuz Zuhria; Tri Shofia Marcellina; Lazuada Nefia Ramahdhani; Avina Khoirunnisa; Davien Yanuar; Mikhail Haq; Rachmad Rifky; Muhammad Ryan Soewito; Muh.Qolbuddin Iqhmatiar; Moch Iqbal Riski (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Optimal nutrition and hydration are crucial factors supporting the growth, health, and performance of young futsal athletes, yet many athletes still exhibit poor eating and hydration behaviors due to limited nutritional knowledge. This study analyzed the effect of a digital nutrition education program on eating and hydration behavior among young futsal athletes at NSM Valafa Academy. A quantitative Pre-Experimental One Group Pretest–Posttest design was used, involving 15 parents/guardians of athletes in the KU-10, KU-13, and KU-16 age groups, selected through total sampling. The intervention consisted of a webinar and a digital poster titled “Isi Piringku Atlet” (My Athlete’s Plate); data were collected via a Google Form questionnaire before and after the intervention. Results showed improved eating and hydration behavior after the program, reflected in breakfast habits, vegetable and fruit consumption, understanding of the Isi Piringku guideline, and drinking habits before and after training. The Wilcoxon Signed-Rank Test showed a significant difference between pre-test and post-test scores (p < 0.05) for both variables. A digital nutrition education program combining webinars and digital posters is therefore an effective, practical, and low-cost strategy for improving eating and hydration behavior among young futsal athletes, and is feasible for implementation as part of a coaching program involving coaches and parents.